Experimental and Numerical Study on the Gravitational Deposition and Coagulation of Aerosols - Yu, Huiyu; Gu, Haifeng; Sun, Zhongning; Zhou, Yanmin; Chen, Junyan; Li, Yingzhi (Frontiers in Energy Research, 2022)
The gravitational deposition and coagulation of aerosols were studied experimentally based on the COSTTHES (Containment Source-Term and Thermal Hydraulics Experiment System) facility and numerically investigated based on a continuous general dynamic equation; the experimental and the numerical results were in good agreement. In the present study, the applicability of the zero-dimensional model for deposition and coagulation of aerosols was verified. A considerable distortion can occur due to the coagulation of the aerosol, which significantly influenced the removal rate of the aerosol with a diameter greater than 0.76 µm, and the dynamic shape factor value of the aerosol used in the present experiment was obtained as 4. In the experimental and numerical studies, it was found that the combined effect of the gravitational deposition and coagulation of the aerosol can increase the number density of the aerosol with specific diameters, and the concentration-increment size would increase as settling continued.